A Description of Experiences of Women and Significant others in Accessing Comprehensive Healthcare in the First 1000 Days of Life Post-conception During COVID-19 in Rural Uganda - Nakate, Mary-Grace; MacKay, Sean; Ndirangu-Mugo, Eunice (BMC Pregnancy and Childbirth, 2022)
COVID-19 presented an unprecedented global public health challenge because of its rapid and relentless spread, and many countries instituted lockdowns to prevent the spread of infection. Although this strategy may have been appropriate to reduce infection, it presented unintended difficulties in rural Uganda, especially in maternal and newborn care. For example, some services were suspended, meaning the nearest health facility was at a considerable distance.